Diffusions in architecture : artificial intelligence and image generators - Campo, Matias del; Ohio Library and Information Network (Hoboken, New Jersey : John Wiley & Sons, Inc., 2024)
Diffusions in Architecture: Artificial Intelligence and Image Generators delves into the impact of Generative AI models and their effect on architecture design and aesthetics. The book presents an in-depth analysis of how these new technologies are revolutionizing the field of architecture and changing the way architects approach their work. The architects presented in the book focus on the application of specific AI techniques and tools used in generative design, such as Diffusion models, Dall-E2, Stable Diffusion, and MidJourney. It discusses how these techniques can generate synthetic images that are both realistic and imaginative, creating new possibilities for architectural design and aesthetics
Cover -- Title Page -- Copyright -- Acknowledgments -- Contents -- Preface -- Prologue -- Suppositions -- Rice or Pasta? Choose Your AI -- Taxonomy -- Diffusions -- The Labors of AI -- An Artificial Tale -- Resistance Is Fertile -- Ontology of Diffusion Models -- Commorancies -- The Etiology of a New Collective Architecture -- Noise, Pixels, and Ancient Metamorphic Rocks -- Timberpunk, Prompt Odyssey, Synthetic Ground, and Other Projects -- Computation Past Forward -- Diffusion Models -- Vestures -- Design as a Latent Condition -- AI, Architecture, and Art -- The Advent of Trees in Architecture -- Five Points of Architecture and AI -- De-Coding Visual Cliches and Verbal Biases -- Light Architecture -- Driftwood Rock -- Digital Spoliare -- Estrangements -- Imago Mundi Imaginibus Mundi -- 3D Diffusion or 3D Disfiguration? -- Role Play -- The Doghouse -- Do Humans Dream of Furry Houses? -- Allies in Exile -- Appendix -- Epilogue -- Glossary -- Contributor Profiles -- References -- Bibliography -- Index -- Image Credits -- About the Author -- EULA
Keywords: Architecture -- Data processing; Architecture -- Computer-aided design; Artificial intelligence